Facial Swelling as a Presenting Sign of Cholangiocarcinoma - Sanjay M. Khaladkar; Darshana Dilip; Vijetha Chanabasanavar; Nagireddy Bethireddy; Purnachandra Lamghare (EMJ Radiology, 2022)
Cholangiocarcinoma is a rare primary malignancy of the biliary tree, which usually presents late in the course of disease with jaundice, upper right quadrant pain, and cachexia. They frequently metastasise in the lungs, liver, bones, adrenals, peritoneum, and retroperitoneal lymph nodes. The incidence of cutaneous dissemination from cholangiocarcinoma is extremely rare, with the scalp being the commonest distant site of skin metastasis. The authors report the case of a 44-year-old female with Stage IV hilar cholangiocarcinoma, who presented primarily with tender facial swelling, prompting investigation and subsequent diagnosis. To the authors’ knowledge, this case is the first report of a cholangiocarcinoma presenting as facial metastasis. It highlights the need for early characterisation of cutaneous lesions, which are likely to be of neoplastic origin using histology, immunohistochemistry, and PET-CT scans, and reminds that biliary tree neoplasms are possible primary malignancies in cases of skin metastasis, especially in the head and neck region.